Detection and Identification of Viral and Viral-Like Diseases Infecting Citrus in the North of West Bank-Palestine - Shalabi, Nuha Jaser Hosni (An-Najah National University, 2017)
Citrus is considered as one of the most fruit trees that are grown in West Bank, it is concentrated in the semi-coastal area specially Tulkarm and Qalqilyah and it is well grown in Nablus and Jenin areas. Due to water scarcity, citrus is counting for only 2.4% of the total fruit tree area, with production of 60,000 tons annually. Although citrus has small area but with larger economic importance.Citrus productivity is associated with many biotic stresses of which some fungi, bacteria, viruses and viriods, which cause several kinds of disease some of these diseases had high economical effect on citrus production.One of these diseases caused by a virus called Citrus tristeza virus (CTV), the virus that caused an epidemic effect on citrus trees leading to their decline. Usually found on those were grafted on sour orange and causes significant reduction of the total yield of the trees. In this study, the prevalence of Citrus tristeza virus (CTV) among growing fields in northern of West Bank was assessed. A total number of 896 plant samples were collected from the four main districts. Serological assays using Double Antibody Sandwich- ELISA (DAS-ELISA) to detect Citrus tristesa virus (CTV) and Citrus psorosis virus(CPsV) on 219 different citrus samlpes, while Direct Tissue Blot Immunoassay (DTBIA) to detect CTV only were applied on 677 of citrus samples. Besides that abiological assays were applied on10 selected samples. CTV was detected in all districts with only 98 out of 869 samples, revealing an incidence of 10.9%. Surprisingly, the results showed that grapefruits and acid less Orange (Faransawi) were CTV free; while, the highest infection was recorded on Pomuelo ,Clementine and Orange cultivar(Valencia). The incidence of infection in each district was varied, Qalqilyah was showed the highest incidence of infectionwith a 23.5%, Nablus was came in the second rank of incidence of infection with a 12%, while Tulkarm was recorded a low incidence of infection with just 6%, the results also recorded a 4% of infection in nurseries, The differences between the four districts, reflecting the type of growing citrus varieties and farming activities. The bioassay (indexing) which was carried at the NARC facilities, were revealed of detection CTV and viriods symptoms by observing Vein corking yellowing and clear veining of the leaves. This study revealed that CTV is still a threat to citrus culture in Palestine. More care should be paid on dissemination and distribution of healthy propagating materials to farmers. The “Direct Tissue Blot Immunoassay” were applied for the first time here in Palestine to monitor the incidence of CTV, and proved its efficiency. Compared with classical DAS-ELISA, the biotechnique DTBIA had proved its simplicity and reliability in mass diagnosis, and thus is highly recommended for nursery monitoring of the virus by the corresponding authorities.
كشف وتحديد الأمراض الفيروسية وشبه الفيروسية التي تصيب الحمضيات في شمال الضفة الغربية